First measurement of the tt[over ] differential cross section dsigma/dM_{tt[over ]} in pp[over ] collisions at sqrt[s]=1.96 TeV. - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present a measurement of the tt[over ] differential cross section with respect to the tt[over ] invariant mass, dsigma/dM_{tt[over ]}, in pp[over ] collisions at sqrt[s]=1.96 TeV using an integrated luminosity of 2.7 fb;{-1} collected by the CDF II experiment. The tt[over ] invariant mass spectrum is sensitive to a variety of exotic particles decaying into tt[over ] pairs. The result is consistent with the standard model expectation, as modeled by PYTHIA with CTEQ5L parton distribution functions.